DISKs : a system for distributed spatial group keyword search on road networks - Luo, Siqiang (2014)
Query (e.g., shortest path) on road networks has been extensively studied. Although most of the existing query processing approaches are designed for centralized environments, there is a growing need to handle queries on road networks in distributed environments due to the increasing query workload and the challenge of querying large networks. In this demonstration, we showcase a distributed system called DISKs (DIstributed Spatial Keyword search) that is capable of efficiently supporting spatial group keyword search (S-GKS) on road networks. Given a group of keywords X and a distance r, an SGKS returns locations on a road network, such that for each returned location p, there exists a set of nodes (on the road network), which are located within a network distance r from p and collectively contains X. We will demonstrate the innovative modules, performance and interactive user interfaces of DISKs.